Interpolymer Complexes of Synthetic, Natural and Semi-Natural Polyampholytes: A Review - Bekturov, E.A.; Moustafine, R.I.; Kudaibergenov, S.E.; Khutoryanskiy, V.V. (KU Publ., 2022)
This review is focused on synthetic, natural and semi-natural polyampholytes and their ability to form interpolymer complexes with other polyelectrolytes and non-ionic polymers. It provides definition, classification and overview of physicochemical properties of polyampholytes. The conformation and phase behaviour of intrinsically disordered proteins and semi-natural polyampholytes derived from aminoacids is discussed. The ability of synthetic, natural and semi-natural polyampholytes to form interpolymer complexes with water- soluble polymers is considered. Most of the research in this area is focused on interpolyelectrolyte complexes of polyampholytes with oppositely charged polyelectrolytes; however, there are also studies demonstrating the formation of hydrogen-bonded complexes. The nature of the complexation is often affected by solution pH and also isoelectric point of polyampholytes. The complexation between polyampholytes and other polymers may lead to formation of colloidal dispersions (nano- and microparticles), liquid-liquid phase separation (called complex coacervation), fully soluble polycomplexes or physically cross-linked gels. A substantial body of studies in this area was focused on the complexes formed by proteins. Application of interpolymer complexes formed by polyampholytes in biotechnology, medicine, encapsulation technologies, separation science, biocatalysis, food science and pharmaceutics is discussed.
Жасанды, табиғи және жартылай табиғи полиамфолиттердің интерполимерлі кешендері: Шолу
Интерполимерные комплексы синтетических, природных и полуприродных полиамфолитов Обзор
Keywords: polyampholytes; polypeptides; proteins; intrinsically disordered proteins (IDPs); intra-macromolecular complexes (intra-MMC); interpolyelectrolyte complexes; drug delivery; complex coacervation; gelatin